RESPONSE OF WEANER PIGS TO FIBRE FEEDSTUFFS SUPPLEMENTED WITH PROBIOTIC COMPLEXES - AKINFALA, E. O.; ADEYEMI, M. A.; ADEBAMBO, T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study was carried out to evaluate the effects of probiotic supplementation on the utilisation of fibre feedstuffs (corn bran (CB), palm kernel cake (PKC) and rice bran (RB)) by weaner pigs for growth and economics of production. Thirty-six crossbred (Large White x Hampshire) pigs of average weight 14.08±0.33 Kg were randomly distributed into six experimental diets. Diets 1, 3 and 5 contained 30% each of CB, PKC and RB respectively while commercial probiotics (Re3) were added at the recommended rate of 0.75 ml/kg of feed into diets 2, 4 and 6 with the same formulation as diets 1, 3 and 5. The experiment lasted for 28 d. Results showed a significant (p<0.05) increase in final body weight and average daily weight gain of pigs fed CB and RB-supplemented diets while those on PKC without probiotics had higher final body weight (27.50 Kg) and daily weight gain (473 g) than pigs on other dietary treatments. The pigs fed a PKC-based diet without probiotics had the best feed:gain (2.90) while those fed RB without probiotics performed the poorest (3.88). Also, the average daily feed intake was highest in PKC without supplementation (1.165 Kg/d) and least in RB with probiotics (0.947 Kg/d). The feed cost/kg gain was highest (₦1082.40) in RB with probiotics and least (₦811.59) in PKC without probiotics. It was concluded that, probiotics supplementation enhanced the performance of pigs fed CB and RB-based diets. Also, the feed cost kg-1 gain was better with pigs fed PKC with and without probiotics supplementation.